Analisis Faktor – Faktor yang Mempengaruhi Kinerja Karyawan : Penelitian Pada Karyawan Sleman City Hall Mall - Ali Mustofa, Muhammad; Subiyanto, Didik; Soni Kurniawan, Ignatius (Coopetition : Jurnal Ilmiah Manajemen, 2024)
The purpose of this study is to evaluate the influence of Education, Training, and Work Environment on Employee Performance and provide strategic insights for human resource management. This study uses a quantitative approach with the census method, involving the entire employee population in Sleman City Mall which totals 114 respondents. Data was collected using a questionnaire with a Likert scale of 1-5 that included variables of training, education, work environment, and employee performance. The questionnaire is distributed through the appropriate media, with clear instructions for filling and returning. The collected data was analyzed using Path Analysis (SEM) with the help of AMOS software, which included initial data processing, preparation of measurement models, construction of structural models, and hypothesis testing to test the relationships between variables. The results of the analysis show that education plays an important role in improving employee abilities and productivity as well as decision-making capacity. Continuous training strengthens technical and non-technical skills and helps employees adapt to industry changes. However, the Work Environment proved to be the most dominant factor, affecting employee motivation, comfort, and productivity. In conclusion, management needs to strategically integrate education, training, and improvement of the work environment to achieve optimal performance. The implications for organizations include the importance of investing in employee education, developing continuous training programs, and creating a conducive work environment. These measures will increase employee productivity, satisfaction, and loyalty, as well as create a sustainable competitive advantage for the organization.